A comparative study of talent development environment between the scottish professional football club and the chinese professional football club - Yang, L.; McEwan, H. (29th Annual Congress of the European College of Sport Science, 2-5 July 2024, Book of Abstracts, 2024)
Abstract Environmental factors are considered to significantly impact football players in the Talent Development process. By using a holistic ecological approach, previous studies mainly focused on the European context. This research compared two youth academies of a Chinese and Scottish football club. The objective set out to explore the differences and similarities between the two academies, and the causes behind the scene. Methods The research took the form of a case study. Given the restrictions of the pandemic, semi-structured interviews and document analysis were the main methods used to collect data. Three participants*i.e. coaches, supporting staff, and managers) from each club were interviewed for one to two hours about the different facets of the environments of Talent Development in each club. Thematic analysis was used to analyze data from interviews and documents. Trustworthiness was ensured through several processes*i.e. a tested theory, member reflection, triangulation). The comparison was conducted after the summary of the results from each case. Results Utilizing a holistic ecological approach, it revealed that the Scottish football club exhibits six key characteristics within its academy: experienced coaches for players of different age groups, strong family support, a national culture promoting football, community-oriented club culture, robust sports science support, and a commitment to long-term player development. In contrast, the Chinese football club features eight characteristics: consistent youth academy investment, collaboration with Japan in football, a long-term player development focus, emphasis on academic learning, administrative support from the club, opportunities for youth players in the first team, limited sports science support, and a lack of family support. Discussion The results highlight a significant similarity in well-structured youth academies between the Scottish and Chinese football clubs. Considering the complex and dynamic process of Talent Development, a well-structured youth academy sets up a solid foundation for players to be trained under the long-term development principle, thus enabling players a consistent pathway and smoother transitions between stages. However, differences in family support and sports science utilization stem from distinct social contexts, including the geographical proximity of families to clubs and the varying developmental levels of sports science in universities between Scotland and China. These disparities influence the level of support available to players in each club. Future research could explore the macro-environmental factors contributing to football disparities between Scotland and China.